Expression of CD90 and P75NTR stem cell markers in ameloblastomas: a possible role in their biological behavior - Fernanda Paula Yamamoto SILVA; Andrielle DIAS; Carolinne Almeida COELHO; Eliete Neves GUERRA; Ana Elizia Mascarenhas MARQUES; Daniel de Almeida DECURCIO; Andrea MANTESSO; Sérgio Elias Vieira CURY; Brunno Santos de Freitas SILVA
Abstract Multicystic and unicystic ameloblastomas are benign odontogenic tumors that present distinct biological behavior. The investigation of stem cells has become an important branch of tumor biology, with several studies addressing the possible role of these cells in tumor growth, angiogenesis, progression, infiltration and invasiveness. This study evaluated the immunohistochemical expression of CD90(Thy-1) and P75NTR stem cell markers in multicystic and unicystic ameloblastomas. Seventeen (17) samples of ameloblastomas (multicystic, n = 10; unicystic, n = 7) were submitted to immunohistochemical reactions and graded semi-quantitatively. The Kolmogorov-Smirnov test was used to verify possible differences in CD90 and P75NTR expressions between multicystic and unicystic ameloblastomas (p < 0.05). CD90 immunostaining was observed in all multicystic ameloblastoma specimens (n = 10), in the cytoplasm of the fibroblasts and vascular endothelial cells of the tumor stroma, near the neoplastic odontogenic epithelia. The staining of stromal CD90 was significantly higher in multicystic than in unicystic ameloblastomas (p = 0.003). Nuclear P75NTR immunostaining was observed in all ameloblastoma specimens. A significant difference was seen in the epithelial staining of P75NTR between multicystic and unicystic types (p = 0.007). The increased expression of CD90 and P75NTR found in multicystic ameloblastomas suggests a behavioral biological difference between multicystic and unicystic ameloblastomas, as well as a difference in ameloblastoma development.